Alexithymic traits, independent of depression and anxiety, are associated with reduced sleep quality. (15th July 2018) - Murphy, Jennifer; Wulff, Katharina; Catmur, Caroline; Bird, Geoffrey
Abstract: Disrupted sleep is a transdiagnostic factor characterising a multitude of psychiatric conditions. Although this is well-recognised, the cause of poor sleep across conditions is unclear. One possibility is that poor sleep is driven by traits which also co-occur with multiple conditions. Previous research suggests that alexithymia (an inability to identify and describe one's emotions) is a candidate trait, as it is linked to poor sleep quality and elevated levels of alexithymia are seen across multiple diagnostic groups. The association between alexithymia and poor sleep quality has been questioned however, with studies arguing that it is depression and anxiety, rather than alexithymia, which impact sleep quality. Problematically, such studies typically utilise measures of depression and anxiety which include items relating to sleep – meaning that apparent associations between depression and anxiety may be due to measurement issues, rather than to depression and anxiety per se. Study 1 confirmed the relationship between alexithymia and subjective sleep quality, whilst Study 2 utilised an independent sample to replicate the association between alexithymia and sleep quality, and to demonstrate that it is not a product of co-occurring depression or anxiety. Results therefore support the suggestion that alexithymia may explain disrupted sleep across multiple psychiatric conditions. Highlights: Examines the relationship between alexithymia and sleep quality Study 1 confirms the relationship between alexithymia and poor sleep quality. Study 2 demonstrates this association is not a product of depression or anxiety.